Efficacy of Attentional Awareness Program in Enhancing Resilience and Wellbeing Among Children - Dr. Asma Riaz Hamdani; Dr. Asma Majeed; Khansa Javaid (`, 2025)
Background: Childhood is a critical period in forming the cognitive, emotional, and psychological foundations that shape an individual’s lifelong well-being. In today’s rapidly changing world, children face a variety of stressors vs and distractions that can impede their development attention awareness, well-being, and overall resilience. By promoting attention skills and resilience, attention awareness programs can provide children with essential tools to cope with challenges and setbacks, developing their ability to cope with challenges and grow from their experiences. Objective: This study aimed to investigate the effectiveness of attentional awareness program as an intervention to enhance mindfulness, resilience and wellbeing among children. Study type, settings and duration: An experimental study was carried out at public sector schools in Faisalabad. This research was based on two phases. Phase-I was the recruitment of participants on baseline measures. Phase-II was experimental study. Recruitment of participants started in April 2023, experimental study was carried out in August 2023 and post-measurements were taken in September, 2023. Results: The results indicate that participation in the attentional awareness program significantly improved wellbeing F (1,34) = 5.45, p <.000, ŋ²p =.14 and attention awareness F (1,34) =125.79, p <.000, ŋ²p=.78 among children. The results revealed that the attention awareness program led to a statistically significant increase in children’s resilience F (1,34) =3.90, p <.00’, ŋ²p =.10. Conclusion: This study underscores the importance of incorporating attentional awareness practices into educational and psychological interventions for children. By practicing them with skills to manage stress, regulate emotions, and enhance focus, attentional awareness programs can contribute to the development of resilient and emotionally well-adjusted individuals, better prepared to face life’s challenges. Key words: Attentional awareness program, mindfulness, Resilience, Wellbeing, Children